Neotropical Otter Lontra longicaudis - Rheingantz, Marcelo; Valenzuela, Alejandro Eduardo Jorge; Botero Botero, A; de Thoisy, Benoit; Trujillo, Fernando; González, Ildemaro; Gallo Reynoso, Juan Pablo; Marmontel, Miriam; Hernández Romero, Pablo Cesar; Rosas Ribeiro, Patricia F; Wallace, Robert; Utreras Bucheli, Victor Manuel
A species closely related to the North American river otter, the Neotropical otter is widely distributed across Latin America. Often found in areas inhabited by the Giant otter, the two species appear to coexist. Fil: Rheingantz, Marcelo. Universidade Federal do Rio de Janeiro; Brasil Fil: Valenzuela, Alejandro Eduardo Jorge. Universidad Nacional de Tierra del Fuego; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Botero Botero, A. Universidad del Quindio; Colombia Fil: de Thoisy, Benoit. No especifíca; Fil: Trujillo, Fernando. No especifíca; Fil: González, Ildemaro. No especifíca; Fil: Gallo Reynoso, Juan Pablo. No especifíca; Fil: Marmontel, Miriam. No especifíca; Fil: Hernández Romero, Pablo Cesar. Laboratorio de Ecologia y Conservacion de Fauna Silvestre Instituto de Ecologia Universidad Nacional Autonoma de Mexico; Fil: Rosas Ribeiro, Patricia F. Universidade do Estado do Rio Grande do Norte; Brasil Fil: Wallace, Robert. Wildlife Conservation Society; Estados Unidos Fil: Utreras Bucheli, Victor Manuel. Wildlife Conservation Society; Estados Unidos